Physical Maltreatment and Its Associated Factors Among Adolescents in Karachi, Pakistan - Lakhdir, Maryam Pyar Ali (Journal of interpersonal violence, 2021)
In many developing countries, physical child maltreatment is considered as an acceptable disciplinary strategy. The aim of this study was to identify factors associated with physical maltreatment among adolescents in Karachi, Pakistan. A survey of 800 adolescents was done using a structured questionnaire adopted by The International Society for the Prevention of Child Abuse and Neglect. Multiple linear regression methods were used to measure the factors associated with child physical maltreatment. The mean physical score was 17.5 ± 4.9, whereas the minimum and maximum score was 11 and 40, respectively. The total variability in physical scores was found to be 42% explained by child’s gender, child’s age, sibling abuse, verbal abuse/ quarreling within family, child’s height, socioeconomic wealth index, marital status, interaction between parental exposure to childhood abuse and physical fighting using hard object, interaction between parental education and age of mother, and interaction between parental history of psychiatric illness and physical fighting by parents.